2013
DOI: 10.1177/0300060513481923
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical levels of matrix metalloproteinase-2 and CD44 variant 6 protein in the diagnosis and lateral cervical lymph node metastasis of papillary thyroid carcinoma

Abstract: Both MMP-2 and CD44v6 might be useful tumour markers for predicting risk of lateral cervical LNM in patients with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…This increases the adhesion, growth, migration, and invasion of tumor cells, ultimately promoting tumor progression [24]. Studies showed that positive MMP-2 expression correlated with the level of CD44v6 protein, which plays a crucial role in tumor progression and may be a significant predictive factor for poor prognosis in cancer patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This increases the adhesion, growth, migration, and invasion of tumor cells, ultimately promoting tumor progression [24]. Studies showed that positive MMP-2 expression correlated with the level of CD44v6 protein, which plays a crucial role in tumor progression and may be a significant predictive factor for poor prognosis in cancer patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is also involved in the regulation of the glycolytic pathway by modulating cellular reduced glutathione and contributes to antioxidant status and drug resistance in cancer cells [37]. In addition, several tumor-specific CD44 variants have been described in previous reports [38,39]; further study is necessary to determine which CD44 variant is expressed in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that thyroid cancer can stimulate the production of MMPs. Several studies have also found that PTC is associated with overexpression of MMP‐1, MMP‐2, MMP‐7, MMP‐9, and MMP‐13 . However, few studies have reported on the correlation between PTC and other MMPs or the regulatory mechanisms of MMP expression in PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also found that PTC is associated with overexpression of MMP-1, MMP-2, MMP-7, MMP-9, and MMP-13. [11][12][13][14][15][16][17] However, few studies have reported on the correlation between PTC and other MMPs or the regulatory mechanisms of MMP expression in PTC. In the current study, we found that MMP-11 played an important role in the development of PTC.…”
Section: Introductionmentioning
confidence: 99%